Objetos lúdicos disponibilizados às crianças de 3 a 5 anos: o que encontramos na educação infantil? - Nicolielo, Maria Elisa [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The goal of this research is to identify and describe the recreational objects, or toys, children’s play and games offered by teachers from a public municipal school of early childhood education in Pederneiras, a city located inland São Paulo State. The research has started with a retrospective look of the childhood concept and of the recreational objects with in the classical era till the modernity, what has allowed to identify how to play was in history and what is its relation with education. In order to understand how the recreational objects have been seen at school we have made a survey of the oficial Brazilian documents related to the childhood education. The benchmark survey has allowed the organization of a half structured questionnaire and the Kobayashi studies (2009, 2011), was the mean used to identify and classify the recreational objects found at school. The data collected in the benchmark survey in the field remark and by the questionnaire have permitted to identify here recreational objects available by teachers in early childhood education of 3 to 5 years old children at the school mentioned and what they think about the theme, on the other hand the studies performed have allowed us to analyse the adaptation and validity of the recreational objects already found

Este trabalho teve por objetivo identificar e descrever os objetos lúdicos, ou seja, brinquedos, brincadeiras e jogos oferecidos pelos educadores de uma escola pública municipal de Educação Infantil da cidade de Pederneiras, interior de São Paulo. Iniciou com um retrospecto da construção do conceito de infância e dos objetos lúdicos da época clássica à contemporaneidade, o que permitiu identificar como o brincar/jogar foi visto na história e qual a sua relação com a educação. Para que se compreenda como os objetos lúdicos são vistos nas escolas, fizemos um levantamento junto aos documentos oficiais brasileiros dirigidos à Educação Infantil. A pesquisa referencial permitiu a elaboração de um questionário semi-estruturado e os estudos de Kobayashi (2009, 2010) foi o instrumento utilizado para a identificação e classificação dos objetos lúdicos encontrados na escola. Os dados coletados, na pesquisa referencial, na observação de campo e por meio do questionário, permitiram identificar os objetos lúdicos disponibilizados pelos (as) professores (as) de Educação Infantil de crianças de 3 a 5 anos na instituição estudada e o que eles pensam a respeito do tema, por outro lado os estudos realizados nos permitiram analisar a adequação e validade dos objetos encontrados
Keywords: Infância; Educação de crianças; Brinquedos; Jogos; Professores alfabetizadores; Children; Education; Toys; Games; Reading teachers